2015
DOI: 10.1088/1475-7516/2015/09/004
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic bubble and domain wall instabilities III: the role of oscillons in three-dimensional bubble collisions

Abstract: Abstract. We study collisions between pairs of bubbles nucleated in an ambient false vacuum. For the first time, we include the effects of small initial (quantum) fluctuations around the instanton profiles describing the most likely initial bubble profile. Past studies of this problem neglect these fluctuations and work under the assumption that the collisions posess an exact SO(2,1) symmetry. We use three-dimensional lattice simulations to demonstrate that for double-well potentials, small initial perturbatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 109 publications
(174 reference statements)
0
49
0
Order By: Relevance
“…(obtained using the method of Ref. [31]). We also include the leading order prediction to compare to an exponential falloff at large φ 0 .…”
mentioning
confidence: 99%
“…(obtained using the method of Ref. [31]). We also include the leading order prediction to compare to an exponential falloff at large φ 0 .…”
mentioning
confidence: 99%
“…Oscillons can be produced during preheating after different models of inflation [7][8][9][10][11], as well as in various types of field theories [12][13][14][15][16][17][18][19]. In [20], it has been shown that they form when a scalar field oscillates in a potential that opens up away from the minimum, i.e.…”
mentioning
confidence: 99%
“…[30][31][32] and the references therein), these studies have not included the effect of inhomogeneities, which would be interesting to explore. See [33][34][35] for related work suggesting that domain walls (neglecting self-gravity) are unstable to perturbations. extent, and not properties of the nonlinear interaction in gravitational wave scattering.…”
Section: Collision Of Point Particlesmentioning
confidence: 99%